2001
DOI: 10.1111/0033-3352.00141
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Jurisdiction Size and Sale Type on Municipal Bond Interest Rates: An Empirical Analysis

Abstract: The authors use data on municipal bond sales in Oregon from 1994 to 1997 to explore whether population (as a proxy for financial-management capacity) and sale type (competitive or negotiated sale) influence interest rates. They find that smaller jurisdictions pay an interest cost penalty in the municipal bond market, and that competitive sales result in significantly lower interest rates compared to negotiated sales. The authors suggest that measures to enhance the financial-management capacity of small govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 16 publications
3
70
0
Order By: Relevance
“…Breaking the data out and studying one particular government is also an interesting exercise. For instance, Fig 10 shows The visual impact of this loss on the graph is small compared to the actual impact losses like this had on public retirement systems across the nation and the world [32], but it drives home an important point about the flexibility of the government finance database. Isolating more stable government revenues through the use of general revenue, rather than total revenue, is likely to be advisable in many situations, and further isolating your data from the impact of intergovernmental revenue by using the "own source" versions of either revenue number is also possible.…”
Section: Resultsmentioning
confidence: 99%
“…Breaking the data out and studying one particular government is also an interesting exercise. For instance, Fig 10 shows The visual impact of this loss on the graph is small compared to the actual impact losses like this had on public retirement systems across the nation and the world [32], but it drives home an important point about the flexibility of the government finance database. Isolating more stable government revenues through the use of general revenue, rather than total revenue, is likely to be advisable in many situations, and further isolating your data from the impact of intergovernmental revenue by using the "own source" versions of either revenue number is also possible.…”
Section: Resultsmentioning
confidence: 99%
“…To establish the theoretical link, we start from the premise that financial management, such as debt policy or accounting practices, affects municipal bond ratings. Simonsen et al (2001) found that financial management matters for bond interest rates after controlling for credit quality (bond ratings) and other variables. Nevertheless, financial management practices also affect municipal bond ratings, as has been claimed by credit rating agencies (Moody's, 2004) and argued by scholars (Crowley & Loviscek, 1996).…”
Section: Gpp Grades and State Go Bond Ratings: The Hypothesesmentioning
confidence: 95%
“…Previous studies showed that population size and growth rate are positively associated with credit ratings (Cluff & Farnham, 1985;Raman, 1981;Rubinfeld, 1973;Simonsen et al, 2001).…”
Section: Socioeconomic Variablesmentioning
confidence: 99%
See 2 more Smart Citations